Upaya Meningkatkan Hasil Belajar IPS melalui Penerapan Model Discovery Learning Siswa Kelas IX.2 SMP Negeri 4 Mataram - Suryadi, Tutik Demaryanti Tri (ALSYS, 2021)
The purpose of this study was to determine the improvement of social studies learning outcomes through the application of the Discovery Learning model for Class IX.2 students of SMP Negeri 4 Mataram in the 2018/2019 academic year. The subjects of this study were students of class IX.2 SMP Negeri 4 Mataram with a total of 32 students consisting of 16 male students and 16 female students. The selection of class IX.2 aims to improve and enhance students' learning activities in social studies learning by applying the Discovery Learning model. Based on the results of the research analysis obtained, it will be concluded that the application of the Discovery Learning model can improve student learning outcomes, especially social studies subjects. This is evident in the initial conditions with an average value of 70.53% then increased in the first cycle with an average value of 75.41% then increased again in the second cycle with an average value of 79.75. While the completeness of student learning outcomes in the initial conditions was 46.88% while in the first cycle was 68.75% and then increased again in the second cycle, namely 90.63%. In addition to the learning model, Discovery Learning can increase teacher activities in guiding and drawing conclusions from the subject matter. While student activities, students can pay attention to the teacher's explanation during the learning process, students are active in asking questions and answering teacher questions.